A Critical Overview of Disability Prevalence and Law in Pakistan - Shaista Naznin; M. Usman Khan (Dialogue Social Science Review (DSSR), 2025)
In Pakistan, disability has different meaning with different barriers of different types that needs different means and approaches to tackle the issue. Social attitude, State policy and outdated disability law are main hurdles in PWDs participation, representation, and inclusion in society. Pakistan ratified UN Convention on the Rights of Persons with Disabilities (UNCRPD) in 2011. This requires Pakistan to adopt UNCRPD standards at national level in its letter and spirit. However, the legislation in Pakistan is mostly incapable to take pace with the emerging modern notion of disability under UNCRPD. In the absence of an appropriate legal framework to address disability issue, superior courts in Pakistan have attempted to interpret and give judgments on various issues brought to it. However, in the absence of purpose-oriented law, court judgments can fill the gap only.